Model-free control of electrically driven robot manipulators using an extended state observer. (October 2020) - Saleki, Amir; Fateh, Mohammad Mehdi
Abstract: This paper deals with the robust control of robot manipulators by presenting a novel voltage-based control approach. For this purpose, an Extended State Observer (ESO) is utilized to estimate the dynamical behaver of the system without any need to use the equations of motion including robot dynamics, actuator dynamics and their parameters in the proposed method. Convergence analysis proves that the estimated parameters converge to actual parameters asymptotically. The boundedness of tracking error is guaranteed through the Lyapunov theorem. Simulation results on an articulated robot driven by permanent magnet DC motors, and experimental implementation on a SCARA robot show that the proposed model-free controller has a satisfactory performance as compared to an adaptive uncertainty estimation-based controller.